2019
DOI: 10.3389/fonc.2019.01434
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length of Circulating Cell-Free DNA and Gastric Cancer in a Chinese Population at High-Risk

Abstract: Background: Telomeres have long been found to be involved in cancer development, while little was known about the dynamic changes of telomere length in carcinogenesis process. Methods: The present study longitudinally investigated telomere alterations of cell-free DNA (cfDNA) in 86 gastric cancer (GC) subjects recruited through a 16-year prospective cohort with 2-4 serums collected before each GC-diagnosis from baseline and three follow-up time-points (a total of 276 samples). As the control, 86 individual-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Given the well-established knowledge that shorter telomeres contribute to cellular senescence [72], both tTL and telomerase activity (TA) have been the subject of research on cancer-related biomarkers. In fact, an increasing body of evidence supports the potential of both serving as diagnostic and prognostic biomarkers for various cancers [73,74]. The underlying hypothesis is that when cellular senescence is combined with excessive environmental burden (for instance UV exposure), the cell may be led to apoptosis.…”
Section: Telomere Length (Tl)mentioning
confidence: 99%
“…Given the well-established knowledge that shorter telomeres contribute to cellular senescence [72], both tTL and telomerase activity (TA) have been the subject of research on cancer-related biomarkers. In fact, an increasing body of evidence supports the potential of both serving as diagnostic and prognostic biomarkers for various cancers [73,74]. The underlying hypothesis is that when cellular senescence is combined with excessive environmental burden (for instance UV exposure), the cell may be led to apoptosis.…”
Section: Telomere Length (Tl)mentioning
confidence: 99%
“…They found that its levels were significantly reduced in patients with no prior treatment when compared to control individuals, suggesting that plasma cf-telDNA levels are associated with breast cancer susceptibility [ 139 ]. In gastric cancer, shortened telomeres were associated with gastric cancer risk [ 134 ], while RTL was found to be significantly lower in endometrial cancer patients [ 135 ]. This data is in accordance with the existence of paradoxically shorter telomeres in patients with cancer.…”
Section: Applications Of Telomeric Dna In Cancer Assessmentmentioning
confidence: 99%
“…Two further studies assessed cfDNA telomere length in gastric [ 90 ] and endometrial cancer [ 91 ]. In gastric cancer, with all measurements from baseline and different follow-up time-points, shortened telomeres were found to be significantly associated with gastric cancer risk (OR = 7.37, 95% CI: 2.06–26.32 for 1 unit shortening) [ 90 ].…”
Section: Application Of Cell-free Repetitive Dna In Liquid Biopsies O...mentioning
confidence: 99%
“…Two further studies assessed cfDNA telomere length in gastric [ 90 ] and endometrial cancer [ 91 ]. In gastric cancer, with all measurements from baseline and different follow-up time-points, shortened telomeres were found to be significantly associated with gastric cancer risk (OR = 7.37, 95% CI: 2.06–26.32 for 1 unit shortening) [ 90 ]. Benati et al evaluated the diagnostic performance of relative telomere length (i.e., telomere repeat copy number to single-gene copy number ratio) in cfDNA and found RTL to be significantly lower in endometrial patients with cancer [ 91 ].…”
Section: Application Of Cell-free Repetitive Dna In Liquid Biopsies O...mentioning
confidence: 99%